Estimated efficiency of uterine cavity suturing in patients during organ-preserving surgery with placenta increta while examining reproductive function in the postpartum period - E. A. Berg; A. G. Yashchuk; I. I. Musin; Yu. N. Fatkullina (Акушерство, гинекология и репродукция)
Aim: to assess the reproductive function of patients who underwent organ-preserving delivery using a modified method of uterine cavity suturing placenta increta.Materials and Methods. There were retrospectively investigated 77 history cases of patients admitted for planned delivery in 2018–2020, subdivided into two groups: Group 1 (control) – 32 patients with uterine scar after previous cesarean section, Group 2 (main) – 45 patients diagnosed with placenta increta further assigned to 2 subgroups – 2A (n = 23) underwent a modified uterine cavity suturing, and subgroup 2B (n = 22) where a linear suturing was used.Results. The groups studied were comparable on anthropometric data and reproductive history. The ultrasound examination of the uterus size 6 months later revealed more prominent changes in main group that might be due to larger volume of excised uterine tissue during surgery. Significant differences in subgroup 2A (uterus length – 54 [48; 62] mm, uterus width – 38 [29; 47] mm; p = 0.036 and p = 0.024, respectively) and subgroup 2B (uterus length – 51 [42; 60] mm, uterus width – 30 [24; 44] mm; p = 0.003 and p < 0.001) vs. control group (uterus length – 60 [55; 66] mm, uterus width – 48 [42; 54] mm) were observed. Magnitude of change in size and shape of the uterus were found in subgroup 2A vs. 2B (p = 0.022 for uterus length, p = 0.004 for uterus width). Examining intrauterine blood flow revealed no significant differences between the groups compared (p > 0.1).Conclusion. Assessing results of the applied new method for uterine cavity suturing in patients with placenta increta showed a marked efficiency in maintaining anatomically most natural shape of the uterus and uterine cavity. Despite the results obtained, the problem of restoring female reproductive function after organ-preserving delivery remains a pressing issue relevant and requires to be further investigated.